Preface - Riedl, Mark; Sukthankar, Gita (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2012)
Welcome to the Eighth AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment (AIIDE’12). Computer games are a staple of today’s popular culture, and have been called the preemi- nent form of entertainment of the 21st century. The computer game industry has become a multibillion- dollar commercial enterprise. Game system require- ments are an important driver of hardware and soft- ware innovation in the computer industry.